أحكام ميراث الحمل بين الفقه الإسلامي و القانون الوضعي - مولاتي, لسعد (جامعة الوادي -University eloued, 2017)
عرفنا الحمل وقلنا أنه ما كان في بطن أو على شجر وهو يعني أيضا الهَوْدج ، ومـــــن الناحيـــة الاصطلاحية المراد به هـــو من كان في رحم أمه حین مـــوت موَرِّثـــه ، ممــن يرث أو يحجب إذا انفصل حیّاً، وأما من الناحيــــة القانونيــــة فالحمل هــــــو البويضة الملقحـــــــة تبدأ حياة الجنين بالإخصاب أي تلقيح الحيـــــوان المنوي لبويضة المــــرأة، وقــــــد اعتبره المشرع الجـــــزائري نهاية حياة الجنين وبدايــة الحياة الإنسانيــــة بتمام ولادتـه حيا لا ببدايتها، وقــد وضعت الشرائع القانونية له الحماية الجنائية منذ لحظة تشكلــــه لأنـه يتمتع بالشخصية القانونية . ويمر الحمل بمـراحل في تكوينــــــه بينها الله في كتابه العزيز، وأما ميراثــــــه مشروع بالكتاب والسنـــة بشرطين الأول: أن يكون الحمل موجـودا حال وفاة مورثــــــه، والثاني: أن يــــولد حيا حتى يصبح أهـــــلا للميراث، وقـــــــــد اختلف فقهاء الشريعــــــة والقانون حــول مسالــــة مـــــــــدة الحمل وعــــدده كما أنهـــــم اختلفوا حــــول إذا ما وقعت له جنايـــة كيف يتحصل على حقوقه. وفي مقدار ما يوقف للحمل من الميراث، وبيّنا كل حالة وفق نموذج حسابي، وكذالك مسألة الوصية الواجبة له كونه مـن الأحفـــــــاد المرتقبين، وقد حذت أغلب القـــوانين العربيــة حذو المشــرع الجزائري فاستمدت أحكام قانـون المواريث من أحكــام الشريعـــة الإسلاميـــة، غير أنها لم تتقيــــد فيها بمــذهب معين. We knew the pregnancy and said that it was not in the belly or on trees, which also means the udder, and in terms of terminology meant to be who was in the womb of his mother when the death of his successor, who inherits or obscures if separated alive, legally speaking pregnancy is fertilized egg begins life fetus fertilization of any sperm insemination of a woman's egg, was considered by the Algerian legislator the end of life of the fetus and the beginning of human life Pettmam was born alive not Bbdaatha, has developed the legal protection of criminal laws have since the moment posed because it has Legal personality. Passing pregnancy stages in its composition, including God in his holy book, and the inheritance project book and the year the first two conditions: that the pregnancy is present if the death of the deceased, and the second to be born alive until it becomes eligible for inheritance, it differed scholars of Sharia law on the issue of the duration of pregnancy and numbering as they differed about whether a felony occurred to him how it obtained the rights. In the amount of stop pregnancy from inheritance, and Pena each case according to a mathematical model, and also the question of due commandment to him being one of the grandchildren potential, have followed most of the Arab laws it follows the Algerian legislature Fastmdt provisions of the inheritance law of the provisions of the Islamic Sharia, but they did not comply with a particular doctrine.
ماستر اسرة
Keywords: الحمل – الميراث – القانون; Pregnancy - inheritance - law